Autoformation en langues : quel guidage pour l'autonomisation ? - Annick RIVENS MOMPEAN; Martine Eisenbeis (Recherches en didactique des langues et des cultures)
A guided self-access environment in English, French as a foreign language and Spanish is open to students in the "Didactics of Foreign Languages" Master's at Lille3 University. This blended environment includes the following elements: a Language Resource Centre with multimedia resources that have been selected and classified according to specific criteria, group sessions such as Learning to Learn workshops or Speaking Practice sessions and a Moodle collaborative e-learning platform. Individual interviews are organised for the students who also have to maintain a logbook of their learning process.Our corpus consists of the answers to a questionnaire completed by students who took part in the blended learning, cross-checked with their logbooks for the semester. An analysis of this corpus indicates that autonomy does not develop equally from the various activities and moreover that different forms of autonomy (general autonomy, language autonomy and learning autonomy) emerge during the learning process. How do these different aspects of autonomy combine? Are they established once and for all, or do they evolve, and if so, how? Are there any predictable steps? Our aim is to understand the tensions that emerge between guidance and autonomy, two notions that may seem contradictory, but which, in the final analysis, appear to be complementary in that certain forms of guidance favour the development of autonomy. Should we consider guidelines as necessary and useful, enabling students to develop appropriate individual strategies? From this analysis, our goal is to determine the essential elements of the learning environment, and the articulation between them, in order to optimise its efficiency for successful, autonomous language learning.